2021
DOI: 10.1109/jxcdc.2021.3131100
|View full text |Cite
|
Sign up to set email alerts
|

Power Performance Analysis of Digital Standard Cells for 28 nm Bulk CMOS at Cryogenic Temperature Using BSIM Models

Abstract: Cryogenic CMOS is a crucial component in building scalable quantum computers, predominantly for interface and control circuitry. Further, high performance computing can also benefit from cryogenic boosters. This necessitates an in-depth understanding of the power and performance trade-offs in cryogenic operation of digital logic. In this paper, we analyze digital standard cells in 28nm High-K Metal Gate (HKMG) CMOS foundry Process Design Kit (PDK). We have developed BSIM4 models of cryogenic CMOS and calibrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Figure 3 shows the temperature dependence of fresh (prestressed) I D -V G and g m characteristics. As reported in the previous literatures, [27][28][29][30][31] it is confirmed that the electrical characteristics are improved with decreasing temperature. In particular, the threshold voltage (V th ) is increased, the subthreshold slope (SS) is improved, and the transconductance (g m ) is improved.…”
Section: Resultssupporting
confidence: 87%
“…Figure 3 shows the temperature dependence of fresh (prestressed) I D -V G and g m characteristics. As reported in the previous literatures, [27][28][29][30][31] it is confirmed that the electrical characteristics are improved with decreasing temperature. In particular, the threshold voltage (V th ) is increased, the subthreshold slope (SS) is improved, and the transconductance (g m ) is improved.…”
Section: Resultssupporting
confidence: 87%
“…However, when temperature falls below 220 K, temperature coefficients of KT1, UTE, and PRT are not a constant anymore but varies with temperature, resulting in large fitting errors for simulating characteristics of MOSFETs using the standard BSIM models at cryogenic temperatures. Therefore, the inclusion of the additional temperature-dependent functions for these coefficients is required in order to improve the fitting precision for MOSFETs operation from 77 K to 300 K. For modeling the performance of MOSFETs at cryogenic temperatures, one has to tune key parameters at each temperature point in order to account for the varying device characteristics across the wide temperature range of 77 K-300 K [17], [31].…”
Section: Modeling Resultsmentioning
confidence: 99%
“…Figure 6. The device output characteristics for iso-overdrive voltage [10] The device transfer characteristics are shown for the linear region is shown in figure 7.…”
Section: The Characteristics Of Cmos Powermentioning
confidence: 99%